Ammonia gas sensing and magnetic permeability of enhanced surface area and high porosity lanthanum substituted Co–Zn nano ferrites. Issue 11 (1st June 2022) - Mugutkar, Anil B.; Gore, Shyam K.; Patange, Sunil M.; Mane, Rajaram S.; Raut, Siddheshwar D.; Shaikh, Shoyebmohamad F.; Ubaidullah, Mohd; Pandit, Bidhan; Jadhav, Santosh S.
Abstract: This work reports magnetic permeability and ammonia gas sensing characteristics of La 3+ substituted Co–Zn nano ferrites possessing chemical formula Co0.7 Zn0.3 Lax Fe2-2x O4 (x = 0–0.1) synthesized by a sol-gel route. Refinement of X-ray diffraction (XRD) patterns of the ferrite powders by the Rietveld technique has revealed the creation of single-phase spinel structure. The tenancy of constituent cations at tetrahedral/octahedral sites was obtained from the refinement of XRD. The crystallite sizes calculated from the W–H method vary from 20 to 24 nm. The scanning electron microscope (SEM) profiles of the ferrite samples were analyzed for the morphological details. The energy dispersive X-ray analysis (EDAX) patterns of the samples were obtained to test the elemental purity of the ferrites within their stoichiometry. The transmission electron microscope (TEM) image of the ferrite (x = 0.1) exhibits the spherical and oval shaped particles with a mean size of 20 nm. Fourier transform infra-red (FTIR) spectra were analyzed to confirm the superseding of La 3+ cations at octahedral sites. The Brunauer-Emmett-Teller (BET) analysis of nitrogen adsorption-desorption isotherms of the ferrites was performed to investigate the porous structure and to determine the surface area of the nanocrystalline ferrites. The oxidation states of the constituent ions were confirmed by means of X-ray photoelectron spectroscopy (XPS). The complex permeability as a function of frequency was studied to explore the effects of structural parameters on the magnetic behaviour of the ferrites. Analysis of gas sensing properties of the ferrites have proved that the Co–Zn–La ferrite with controlled La composition can be utilized as an effective ammonia gas sensing material in commercial gas sensors.